Effects of the Electron-Deficient Third Components in n-Type Terpolymers on Morphology and Performance of All-Polymer Solar Cells - Liu, Bin; Sun, Huiliang; Koh, Chang Woo; Su, Mengyao; Tu, Bao; Tang, Yumin; Liao, Qiaogan; Wang, Junwei; Yang, Wanli; Meng, Hong; Woo, Han Young; Guo, Xugang (Organic Materials, 2020)
Compared with p-type terpolymers, less effort has been devoted to n-type analogs. Herein, we synthesized a series of n-type terpolymers via incorporating three electron-deficient third components including thienopyrroledione (TPD), phthalimide, and benzothiadiazole into an imide-functionalized parent n-type copolymer to tune optoelectronic properties without sacrificing the n-type characteristics. Due to effects of the third components with different electron-accepting ability and solubility, the resulting three polymers feature distinct energy levels and crystallinity. In addition, heteroatoms (S, O, and N) attached on the third components trigger intramolecular noncovalent interactions, which can increase molecule planarity and have a significant effect on the packing structures of the polymer films. As a result, the best power conversion efficiency of 8.28% was achieved from all-polymer solar cells (all-PSCs) based on n-type terpolymer containing TPD. This is contributed by promoted electron mobility and face-on polymer packing, showing the pronounced advantages of the TPD used as a third component for thriving efficient n-type terpolymers. The generality is also successfully validated in a benchmark polymer donor/acceptor system by introducing TPD into the benchmark n-type polymer N2200. The results demonstrate the feasibility of introducing suitable electron-deficient building blocks as the third components for high-performance n-type terpolymers toward efficient all-PSCs.
Keywords: n-type terpolymers; electron-deficient building blocks; bulk morphology; imide-functionalized heteroarenes; all-polymer solar cells